Re-visioning silk through Amami Ōshima = 「奄美大島を通して見た絹の再考 - Onaga, Lisa (KHL Printing Co., Ltd, 2021)
This project is a collaboration between a historian of science (Lisa Onaga), a design historian (Laura Forlano), a textile artist (Galina Mihaleva), and a literary historian (Anne McKnight). It takes its inspiration from pattern books in fabric stores. These pattern books catalog options that sewers can use to customize their garments and are also inspired by Edo-era design books that kimono buyers would peruse when commissioning their own silk kimonos. The essays contextualize a wearable prototype, made of silk from a southern island, Amami-Ōshima situated in the East China Sea between Japan, Okinawa and China. Part I of the chapbook contains essays that give a historical context. Part II contains highly magnified microscopic images of the silk that show detailed patterns that draw on the natural world. By recasting our eyes upon Amami-Ōshima, we are forced to consider a different history of silk-making that encourages a reflection upon historical assumptions about silk in Japan, from fabric to sutures to protein. The title Re-Visioning Silk thus refers to both a renewed view of highly familiar silk and a refashioning of how we have recounted the story of silk, tied to imperial and liberal capital production. This collaborative project serves as a springboard for the identification, documenting, and narrating of silk in less familiar settings and spaces.